IDNLearn.com is the perfect place to get answers, share knowledge, and learn new things. Discover prompt and accurate answers from our experts, ensuring you get the information you need quickly.
Sagot :
Let's solve the polynomial equation [tex]\( 4x^4 - 36x^2 = 0 \)[/tex] by factoring and then verify the solutions by substitution.
### Step 1: Set the Equation to Zero
We start with the polynomial equation:
[tex]\[ 4x^4 - 36x^2 = 0 \][/tex]
### Step 2: Factor Out the Greatest Common Factor
First, we look for the greatest common factor (GCF) that can be factored out. Both terms have a common factor of [tex]\( 4x^2 \)[/tex]:
[tex]\[ 4x^4 - 36x^2 = 4x^2(x^2 - 9) \][/tex]
### Step 3: Further Factorization
Next, we notice that the expression [tex]\( x^2 - 9 \)[/tex] is a difference of squares, which can be factored as follows:
[tex]\[ x^2 - 9 = (x - 3)(x + 3) \][/tex]
Therefore, our factored equation becomes:
[tex]\[ 4x^2(x - 3)(x + 3) = 0 \][/tex]
### Step 4: Set Each Factor to Zero
To find the solutions, we set each factor equal to zero:
[tex]\[ 4x^2 = 0 \quad \text{or} \quad x - 3 = 0 \quad \text{or} \quad x + 3 = 0 \][/tex]
### Step 5: Solve Each Equation
- For [tex]\( 4x^2 = 0 \)[/tex]:
[tex]\[ x^2 = 0 \quad \Rightarrow \quad x = 0 \][/tex]
- For [tex]\( x - 3 = 0 \)[/tex]:
[tex]\[ x = 3 \][/tex]
- For [tex]\( x + 3 = 0 \)[/tex]:
[tex]\[ x = -3 \][/tex]
So the solutions to the equation [tex]\( 4x^4 - 36x^2 = 0 \)[/tex] are:
[tex]\[ x = 0, 3, -3 \][/tex]
### Step 6: Check by Substitution
We will verify each solution by substituting it back into the original equation [tex]\( 4x^4 - 36x^2 = 0 \)[/tex]:
- For [tex]\( x = 0 \)[/tex]:
[tex]\[ 4(0)^4 - 36(0)^2 = 0 - 0 = 0 \quad \text{(True)} \][/tex]
- For [tex]\( x = 3 \)[/tex]:
[tex]\[ 4(3)^4 - 36(3)^2 = 4(81) - 36(9) = 324 - 324 = 0 \quad \text{(True)} \][/tex]
- For [tex]\( x = -3 \)[/tex]:
[tex]\[ 4(-3)^4 - 36(-3)^2 = 4(81) - 36(9) = 324 - 324 = 0 \quad \text{(True)} \][/tex]
Each substitution checks out, confirming that the solutions [tex]\( x = 0, 3, \text{ and } -3 \)[/tex] are correct.
### Summary
We have factored and solved the polynomial equation [tex]\( 4x^4 - 36x^2 = 0 \)[/tex], and verified the solutions by substitution. The solutions are:
[tex]\[ x = 0, 3, -3 \][/tex]
### Step 1: Set the Equation to Zero
We start with the polynomial equation:
[tex]\[ 4x^4 - 36x^2 = 0 \][/tex]
### Step 2: Factor Out the Greatest Common Factor
First, we look for the greatest common factor (GCF) that can be factored out. Both terms have a common factor of [tex]\( 4x^2 \)[/tex]:
[tex]\[ 4x^4 - 36x^2 = 4x^2(x^2 - 9) \][/tex]
### Step 3: Further Factorization
Next, we notice that the expression [tex]\( x^2 - 9 \)[/tex] is a difference of squares, which can be factored as follows:
[tex]\[ x^2 - 9 = (x - 3)(x + 3) \][/tex]
Therefore, our factored equation becomes:
[tex]\[ 4x^2(x - 3)(x + 3) = 0 \][/tex]
### Step 4: Set Each Factor to Zero
To find the solutions, we set each factor equal to zero:
[tex]\[ 4x^2 = 0 \quad \text{or} \quad x - 3 = 0 \quad \text{or} \quad x + 3 = 0 \][/tex]
### Step 5: Solve Each Equation
- For [tex]\( 4x^2 = 0 \)[/tex]:
[tex]\[ x^2 = 0 \quad \Rightarrow \quad x = 0 \][/tex]
- For [tex]\( x - 3 = 0 \)[/tex]:
[tex]\[ x = 3 \][/tex]
- For [tex]\( x + 3 = 0 \)[/tex]:
[tex]\[ x = -3 \][/tex]
So the solutions to the equation [tex]\( 4x^4 - 36x^2 = 0 \)[/tex] are:
[tex]\[ x = 0, 3, -3 \][/tex]
### Step 6: Check by Substitution
We will verify each solution by substituting it back into the original equation [tex]\( 4x^4 - 36x^2 = 0 \)[/tex]:
- For [tex]\( x = 0 \)[/tex]:
[tex]\[ 4(0)^4 - 36(0)^2 = 0 - 0 = 0 \quad \text{(True)} \][/tex]
- For [tex]\( x = 3 \)[/tex]:
[tex]\[ 4(3)^4 - 36(3)^2 = 4(81) - 36(9) = 324 - 324 = 0 \quad \text{(True)} \][/tex]
- For [tex]\( x = -3 \)[/tex]:
[tex]\[ 4(-3)^4 - 36(-3)^2 = 4(81) - 36(9) = 324 - 324 = 0 \quad \text{(True)} \][/tex]
Each substitution checks out, confirming that the solutions [tex]\( x = 0, 3, \text{ and } -3 \)[/tex] are correct.
### Summary
We have factored and solved the polynomial equation [tex]\( 4x^4 - 36x^2 = 0 \)[/tex], and verified the solutions by substitution. The solutions are:
[tex]\[ x = 0, 3, -3 \][/tex]
We value your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. IDNLearn.com is your reliable source for answers. We appreciate your visit and look forward to assisting you again soon.